2020
DOI: 10.1101/2020.12.19.423595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How hot is the hot zone? Computational modelling clarifies the role of parietal and frontoparietal connectivity during anaesthetic-induced loss of consciousness

Abstract: In recent years, specific cortical networks have been proposed to be crucial for sustaining consciousness, including the posterior hot zone and frontoparietal resting state networks (RSN). Here, we computationally evaluate the relative contributions of three RSNs – the default mode network (DMN), the salience network (SAL), and the central executive network (CEN) – to consciousness and its loss during propofol anaesthesia. Specifically, we use dynamic causal modelling (DCM) of 10 minutes of high-density EEG re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Together, our study provides an analytic framework based on graph-theoretical tools to locate the NCC architecture, which complements our understanding about the anatomical footprints underlying consciousness by demonstrating their superior ability not only in functional integration, but also in dynamic functional diversification with modular processors. Furthermore, our results showed that the NCC candidates are not limited within the posterior cortical regions, but are distributed in wide-spread frontal-parietal cortices, which contribute to the ongoing discussion of whether the NCC are residing in the anterior or posterior regions 37,38 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Together, our study provides an analytic framework based on graph-theoretical tools to locate the NCC architecture, which complements our understanding about the anatomical footprints underlying consciousness by demonstrating their superior ability not only in functional integration, but also in dynamic functional diversification with modular processors. Furthermore, our results showed that the NCC candidates are not limited within the posterior cortical regions, but are distributed in wide-spread frontal-parietal cortices, which contribute to the ongoing discussion of whether the NCC are residing in the anterior or posterior regions 37,38 .…”
Section: Discussionsupporting
confidence: 57%
“…Notably, the medial prefrontal region exhibited reduction in both FCS and temporal MV associated with propofol anesthesia, indicating a crucial role of this anterior cluster in contributing to conscious experience. Taking together, these observations provide evidence for the pivotal contribution of the identified putative NCC, which covered most key structures predicted by both GNW and IIT, in supporting human consciousness, and more importantly, highlight the potential differential roles between prefrontal GNW regions and posterior IIT regions during propofolinduced loss of consciousness 37 .…”
Section: Discussionmentioning
confidence: 53%